2016
DOI: 10.1007/s00226-016-0856-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of air plasma treatment at atmospheric pressure on thermally modified wood surfaces

Abstract: This study tests the hypothesis that thermal modification of wood influences the effectivity of air plasma treatment. Micro-veneers of European beech, Scots pine and Norway spruce were thermally modified at two different temperatures and subsequently plasma-treated for 1 and 3 s. The veneer surfaces were characterized in terms of morphology, wetting behaviour and surface chemistry. No severe changes in the veneer surfaces due to plasma treatment were observed by scanning electron microscopy. Plasma treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
3
24
0
3
Order By: Relevance
“…However, thermally modified beech veneers show a more pronounced effect in terms of water uptake, melamine uptake, and the corresponding WPG when plasmatreated as unmodified beech veneers, which is reflected in the dimensional stability of plywood. This behavior is attributed to the hydrophobic character of thermally modified wood products [9], which hampers the uptake of water and water-based modification agents into the bulk along with an over-proportional plasma effect in comparison to unmodified beech, as has already been reported for thermally modified wood specimens in comparison to unmodified ones [38].…”
Section: Discussionmentioning
confidence: 76%
“…However, thermally modified beech veneers show a more pronounced effect in terms of water uptake, melamine uptake, and the corresponding WPG when plasmatreated as unmodified beech veneers, which is reflected in the dimensional stability of plywood. This behavior is attributed to the hydrophobic character of thermally modified wood products [9], which hampers the uptake of water and water-based modification agents into the bulk along with an over-proportional plasma effect in comparison to unmodified beech, as has already been reported for thermally modified wood specimens in comparison to unmodified ones [38].…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, heat treated particles and heat treated veneers were used for this study. Principally, plasma treatment caused the same effect of adhesive distribution on heat treated beech veneers as on untreated beech, pine (Pinus sylvestris) and spruce (Picea abies) veneers, but the effect on the heat treated veneers was more pronounced (Altgen et al 2016).…”
Section: Resultsmentioning
confidence: 92%
“…Wood treatment by air plasma for 1 and 3 s increased the surface wettability and free energy which led to increased adhesion of urea–formaldehyde. It was suggested that the enrichment of the lignin by carboxylic groups contributed to the surface polarity and wettability (45).…”
Section: Discussionmentioning
confidence: 99%